2000
DOI: 10.1002/1097-0231(20000815)14:15<1337::aid-rcm9>3.0.co;2-b
|View full text |Cite
|
Sign up to set email alerts
|

Compound-specific isotope analysis. Application to archaelogy, biomedical sciences, biosynthesis, environment, extraterrestrial chemistry, food science, forensic science, humic substances, microbiology, organic geochemistry, soil science and sport

Abstract: The isotopic composition, for example, 14C/12C, 13C/12C, 2H/1H, 15N/14N and 18O/16O, of the elements of matter is heterogeneous. It is ruled by physical, chemical and biological mechanisms. Isotopes can be employed to follow the fate of mineral and organic compounds during biogeochemical transformations. The determination of the isotopic composition of organic substances occurring at trace level in very complex mixtures such as sediments, soils and blood, has been made possible during the last 20 years due to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
90
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 123 publications
(91 citation statements)
references
References 173 publications
0
90
0
1
Order By: Relevance
“…Using 14 C content in fatty acids, we could better discuss the biogeochemical cycle and fates of the terrestrial organic matter in the soil system. Although stable carbon isotopic composition (e.g., Hayes et al, 1990;Huang et al, 1996;Naraoka et al, 1999;Lichtfouse, 2000) and radiocarbon analyses (Pearson et al, 2001;Uchida et al, 2000Uchida et al, , 2001Smittenberg et al, 2006) of lipid class compounds have been reported in sediments, radiocarbon analysis of individual organic molecules has rarely been conducted in soil samples. Lichtfouse et al (1997a, b) determined molecular distribution, 13 C and 14 C of hydrocarbon fractions from modern soil samples, and provided some evidence on their fossil fuel origin.…”
Section: Introductionmentioning
confidence: 99%
“…Using 14 C content in fatty acids, we could better discuss the biogeochemical cycle and fates of the terrestrial organic matter in the soil system. Although stable carbon isotopic composition (e.g., Hayes et al, 1990;Huang et al, 1996;Naraoka et al, 1999;Lichtfouse, 2000) and radiocarbon analyses (Pearson et al, 2001;Uchida et al, 2000Uchida et al, , 2001Smittenberg et al, 2006) of lipid class compounds have been reported in sediments, radiocarbon analysis of individual organic molecules has rarely been conducted in soil samples. Lichtfouse et al (1997a, b) determined molecular distribution, 13 C and 14 C of hydrocarbon fractions from modern soil samples, and provided some evidence on their fossil fuel origin.…”
Section: Introductionmentioning
confidence: 99%
“…In recent investigations, we have used compound-specific isotope analysis (CSIA, Hayes et al, 1990, reviewed by Lichtfouse, 2000) and biomarkers in order to study the sources and the formation of soil humic substances (Lichtfouse, 1998, Lichtfouse et al, 1997a,b, Lichtfouse et al, 1998a. More specifically, crop labelling experiments using 13 C-enriched carbon from maize have allowed to calculate and to predict the turnover of individual soil n-alkanes (Lichtfouse, 1995, Lichtfouse, 1997b.…”
Section: Introductionmentioning
confidence: 99%
“…Developments in GC-IRMS (Matthews and Hayes 1978;Freeman et al 1990;Lichtfouse 2000) have enabled CSIA techniques to be applied in a wide range of studies of hydrocarbons_ENREF_5_ENREF_6. It has been used to aid source rock and oil correlations (Asif et al 2009), source-apportioned polycyclic aromatic hydrocarbon (PAH) emissions (McRae et al 1996), distinguishing gasoline samples (Smallwood et al 2002), and many others reviewed elsewhere (MeierAugenstein 1999;Philp 2007;Thullner et al 2012;Négrel et al 2012).…”
Section: Introductionmentioning
confidence: 99%